HPLC-ESIMSn Profiling, Isolation, Structural Elucidation, and Evaluation of the Antioxidant Potential of Phenolics from Paepalanthus geniculatus - do Amaral, Fabiano Pereira [UNESP]; Napolitano, Assunta; Masullo, Milena; Santos, Lourdes Campaner dos [UNESP]; Festa, Michela; Vilegas, Wagner [UNESP]; Pizza, Cosimo; Piacente, Sonia (Amer Chemical Soc, 2012)
The methanol extract of the flowers of Paepalanthus geniculatus Kunth. showed radical-scavenging activity in the TEAC assay. An analytical approach based on HPLC:ESIMSn was applied to obtain the metabolite profile of this extract and led to the rapid identification of 19 polyphenolic compounds comprising flavonoids and naphthopyranones. The new naphthopyranone (10, 16), quercetagetin (1, 5, 7, 13), and galetine derivatives (9, 11, 17, 19), and a flavonol glucoside cyclodimer in the truxillate form (12), were identified. Compounds 2, 6, and 7 showed the highest antioxidant capacity and ability to affect the levels of intracellular ROS in human prostate cancer cells (PC3).